2023
DOI: 10.1371/journal.pone.0291427
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in the general population of Mongolia: Normative data on WHOQOL-BREF

Enkhjin Bat-Erdene,
Tetsuya Hiramoto,
Enkhnaran Tumurbaatar
et al.

Abstract: No data on the quality of life (QOL) of the general population are available for Mongolia. This study aimed to determine normative data on the World Health Organization Quality of Life-Brief Version (WHOQOL-BREF) in the general population of Mongolia. This nationwide, population-based, cross-sectional study was conducted in 48 sampling centers across Mongolia in 2020. We used the WHOQOL-BREF and the Hospital Anxiety and Depression Scale (HADS) in our study and evaluated their associations with vital signs, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While some households within Ulaanbaatar's ger areas have transitioned to conventional houses, comprehensive central utility systems, apart from electricity, remain lacking. Our previous study found that urban dwellers, particularly those in ger areas, experience lower physical quality of life compared to their rural counterparts 35 . These findings emphasize the need for targeted interventions and support services for urban dwellers, particularly who live in ger areas.…”
Section: Discussionmentioning
confidence: 90%
“…While some households within Ulaanbaatar's ger areas have transitioned to conventional houses, comprehensive central utility systems, apart from electricity, remain lacking. Our previous study found that urban dwellers, particularly those in ger areas, experience lower physical quality of life compared to their rural counterparts 35 . These findings emphasize the need for targeted interventions and support services for urban dwellers, particularly who live in ger areas.…”
Section: Discussionmentioning
confidence: 90%
“…The observed disparity may stem from cultural differences, as more than a third of Mongolian citizens lead a nomadic lifestyle, distinct from an urbanized lifestyle. 25 Another contributing factor might be the fear and anxiety instigated by the COVID-19 pandemic that peaked during the research. 26 28 This phenomenon might have influenced higher scores in specific symptom-related items, such as fever or fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple examples in the literature where HRQoL questionnaires have been employed. For example, EQ-5D-5L has been employed by the authors of [17][18][19][20], SF-36 by [21][22][23][24], WHOQOL-BREF by [25][26][27], EORTC QLQ-C30 by [28][29][30][31], QLQ-CLL17 by [31], and FACT-based questionnaires by [32][33][34][35][36]. The analysis of HRQoL data is most frequently based on descriptive statistics, standard correlation analysis, and inferential statistics (see, e.g., [37]).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of HRQoL data is most frequently based on descriptive statistics, standard correlation analysis, and inferential statistics (see, e.g., [37]). For instance, the correlation (Pearson, Spearman) between HRQoL scores and demographic, clinical, biological, and other parameters was assessed by the authors of [18,23,[25][26][27]29,35,36]. HRQoL scores were compared either among different subgroups of patients [17,18,21,22,24,30,32] or between the subgroups of patients and controls [20,22,23,25,27,31].…”
Section: Introductionmentioning
confidence: 99%